The Issue of Food Security in Cuba - José Alvarez (EDIS)
Since the establishment of the food rationing system in 1962, the issue of food security has been an important one in Cuban life. This fact sheet tries to provide an answer to the question: Are Cubans adequately fed? This is EDIS document FE483, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published July 2004.